2023
DOI: 10.3390/plants12091748
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Components in Horticultural Crops: Chemical Diversity and Usage of Metabolic Engineering for Industrial Applications

Abstract: Plants produce an incredible variety of volatile organic compounds (VOCs) that assist the interactions with their environment, such as attracting pollinating insects and seed dispersers and defense against herbivores, pathogens, and parasites. Furthermore, VOCs have a significant economic impact on crop quality, as well as the beverage, food, perfume, cosmetics and pharmaceuticals industries. These VOCs are mainly classified as terpenoids, benzenoids/phenylpropanes, and fatty acid derivates. Fruits and vegetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 188 publications
(262 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have also indicated that horticultural crops differ from each other for biochemical composition even in genotypes and cultivars of the same species [19][20][21][22]. differences and aroma are strongly cultivar dependent in horticultural crops [23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also indicated that horticultural crops differ from each other for biochemical composition even in genotypes and cultivars of the same species [19][20][21][22]. differences and aroma are strongly cultivar dependent in horticultural crops [23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The primary mechanism of aromatherapy is associated with the limbic system of the brain (Cui et al, 2022;Kagawa et al, 2003), where aromatic compounds stimulate olfactory cells, triggering rapid CNS responses (Spors et al, 2006;Tabert et al, 2007). The olfactory system converts chemical signals into sensations, which involves the olfactory organs, olfactory bulbs (the primary olfactory centers in the brain), and olfactory nerves (Abbas et al, 2023;Angelucci et al, 2014;Tabert et al, 2007). Therefore, when the aroma of EOs enters the human nose, it stimulates olfactory cells to convert the aromatic information into chemical signals, which are transmitted to the limbic system of the brain by the olfactory nerves, affecting the autonomic nervous system (ANS) and endocrine system.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of fragrant elements elevates the value of crops, capturing consumer interest and enabling premium pricing in the market. Notably, aromatic or fragrant rice stands out in both local and international markets due to its exceptional grain quality and enchanting aroma, resulting in its sale at a premium price (Abbas et al, 2023). The aroma holds great significance in determining the quality of the cereal and greatly enhances its potential value in the global market (Nayak et al, 2002;Verma and Srivastav, 2016).…”
Section: Introductionmentioning
confidence: 99%